Factors Associated with Intergenerational Occupational Mobility in Farming Sector in Coastal and Tribal Districts of Odisha of India - Jena, Anshuman; Kanungo, Aditya Prasad (Indian Journal of Extension Education, 2021)
In India, land-based livelihoods of small and marginal farmers are increasingly becoming unsustainable, since their land has not been able to support the family’s basic food requirements. This causes large-scale migration of rural youth from farming to non-farming sector which has caused concern among the country’s policy makers as such a trend, if not checked, is likely to affect the future agricultural activities in future. The need for focusing on the welfare of farmers has gained prominence. The study was carried out from July 2016 to March 2018 with a comparative analysis among the respondents of coastal district (Jagatsinghpur) and tribal district (Mayurbhanj) of Odisha state of India with the total sample of 480 respondents out of which 240 each from tribal and coastal district including 120 each from first and second generation, selected through random sampling. The result revealed that the independent variables like size of land holding, average annual income, and cosmopoliteness in tribal area and the variables like education, family size, average annual income and cosmopoliteness in coastal area had contributed the highest variance to the consequent variable intergenerational occupational mobility.
Keywords: Coastal; Farming; Intergenerational; Mobility; Occupational; Tribal